RoSCAs in Egypt: A Banking Institution or a Commitment Device? - Dina Rabie (University of Hamburg, Institute of Law and Economics (ILE), 2021)
Rotating Savings and Credit Associations (RoSCAs) is a widely spread informal financial institution in developing countries. This paper examines how access to formal banking (or lack thereof), impatience and self-control are correlated with individuals' decisions to join RoSCAs. The paper employs an incentivized experiment to elicit impatience and a questionnaire to measure bank access, self-control and RoSCA participation among university employees in Cairo (Egypt). Findings indicate that access to formal banking significantly decreases the likelihood of RoSCA participation. In addition, behavioural attitudes partially (self-control but not impatience) correlates with the RoSCA participation decision. Conditional on RoSCA participation, behavioural attitudes towards self-control and impatience are significant correlates of whether an individual is a saver or a borrow in the informal institution.
Keywords: C91; D14; O17; 330; RoSCAs; RoSCA rank; informal banking; impatience; self-control